2023
DOI: 10.3847/1538-4357/aca8a1
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Enrichment of the Milky Way Disk Evaluated Using Conditional Abundances

Abstract: Chemical abundances of Milky Way disk stars are empirical tracers of its enrichment history. However, they capture joint-information that is valuable to disentangle. In this work, we quantify how individual abundances evolve across the present-day Galactic radius, at fixed supernovae contribution ([Fe/H], [Mg/Fe]). We use 18,135 Apache Point Observatory Galactic Evolution Experiment Data Release 17 red clump stars and 7943 GALactic Archaeology with HERMES Data Release 3 main-sequence stars to compare the abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The majority of α, light odd-Z, and Fepeak elements (the elements observed by APOGEE) are dominantly produced by K = 2 sources, with one being a prompt process or mix of prompt processes and one being a delayed process or mix of delayed processes. This is substantiated by theoretical yields (e.g., Rybizki et al 2017;Anderson 2019) and past successful data-driven models (e.g., Ness et al 2019;G22;Ting & Weinberg 2022;W22;Ratcliffe & Ness 2023). In this paper, we therefore assume that K 2, though KPM could in principle be implemented with K = 1.…”
Section: The K-process Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…The majority of α, light odd-Z, and Fepeak elements (the elements observed by APOGEE) are dominantly produced by K = 2 sources, with one being a prompt process or mix of prompt processes and one being a delayed process or mix of delayed processes. This is substantiated by theoretical yields (e.g., Rybizki et al 2017;Anderson 2019) and past successful data-driven models (e.g., Ness et al 2019;G22;Ting & Weinberg 2022;W22;Ratcliffe & Ness 2023). In this paper, we therefore assume that K 2, though KPM could in principle be implemented with K = 1.…”
Section: The K-process Modelmentioning
confidence: 85%
“…These works, as well as Ting & Weinberg (2022) and Ratcliffe & Ness (2023), find that the Milky Way stellar abundances are well fit by two components, grounded in [Fe/H] and [Mg/Fe], down to residuals of 0.01-0.03 dex for the most precisely measured elements and 0.05-0.1 dex for elements (such as Na, C, and Ce) with large measurement errors. Simultaneously, Frankel et al (2018) and Ness et al (2022) have found that disk abundances are also well described by a two-component model of birth radius and age.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…2e). Furthermore, at the early stage (8-11 Gyr) of Milky Way, there is a quick steepening in [Fe/H] and [O/Fe] gradient, linked to the effect of the GSE merger event [22,24], slighter later (by ∼ 0.5 Gyr, see Fig. A4) than the epoch based on the LAMOST [27,28] and APOGEE [29,30] data [22,23].…”
Section: Temporal Evolution Of Radial Abundance Gradientmentioning
confidence: 95%
“…The oxygen enrichment and metallicity depletion ([Fe/H]) strongly suggest that Sgr have influenced the evolution of our Galaxy in the past few billion years. Previous studies on the Gaia-Enceladus/Sausage (GSE) have highlighted the significant role of massive mergers in shaping the Galactic disc and altering the radial metallicity gradient in the past 8-11 Gyr [21][22][23][24]. To study the influence of minor merger events (Sgr accretion) on the radial metallicity gradient during the later stages of Galaxy evolution.…”
Section: Temporal Evolution Of Radial Abundance Gradientmentioning
confidence: 99%